Multimodal Eph/Ephrin signaling controls several phases of urogenital development - Peuckert, Christiane; Aresh, Bejan; Holenya, Pavlo; Adams, Derek; Sreedharan, Smitha; Porthin, Annika; Andersson, Louise; Pettersson, Hanna; Wölfl, Stefan; Klein, Rüdiger; Oxburgh, Leif; Kullander, Klas (Kidney international, 2016)
A substantial portion of the human population is affected by urogenital birth defects resulting from a failure in ureter development. Although recent research suggests roles for several genes in facilitating the ureter/bladder connection, the underlying molecular mechanisms remain poorly understood. Signaling via Eph receptor tyrosine kinases is involved in several developmental processes. Here we report that impaired Eph/Ephrin signaling in genetically modified mice results in severe hydronephrosis caused by defective ureteric bud induction, ureter maturation, and translocation. Our data imply that ureter translocation requires apoptosis in the urogenital sinus and inhibition of proliferation in the common nephric duct. These processes were disturbed in EphA4/EphB2 compound knockout mice and were accompanied by decreased ERK-2 phosphorylation. Using a set of Eph, Ephrin, and signaling-deficient mutants, we found that during urogenital development, different modes of Eph/Ephrin signaling occur at several sites with EphrinB2 and EphrinA5 acting in concert. Thus, Eph/Ephrin signaling should be considered in the etiology of congenital kidney and urinary tract anomalies.
Published online 22 June 2016
Gesehen am 13.10.2020